2005
DOI: 10.1111/j.1529-8817.2005.04188.x
|View full text |Cite
|
Sign up to set email alerts
|

A GENETIC MARKER TO SEPARATEEMILIANIA HUXLEYI(PRYMNESIOPHYCEAE) MORPHOTYPES1

Abstract: Emiliania huxleyi (Lohm.) Hay and Mohler is a ubiquitous unicellular marine alga surrounded by an elaborate covering of calcite platelets called coccoliths. It is an important primary producer involved in oceanic biogeochemistry and climate regulation. Currently, E. huxleyi is separated into five morphotypes based on morphometric, physiological, biochemical, and immunological differences. However, a genetic marker has yet to be found to characterize these morphotypes. With the use of sequence analysis and dena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 25 publications
1
78
0
Order By: Relevance
“…Studies on E. huxleyi , which tend to show differing geographic and sometimes depth distributions (Van Bleijswijk et al 1991. Schroeder et al (2005) recently identified a genetic marker that confirmed the genetic basis for discrimination of these North Atlantic morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on E. huxleyi , which tend to show differing geographic and sometimes depth distributions (Van Bleijswijk et al 1991. Schroeder et al (2005) recently identified a genetic marker that confirmed the genetic basis for discrimination of these North Atlantic morphotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This inference has been supported by a range of culture experiment work, (e.g. Brand, 1982;Young and Westbroek, 1991), and molecular genetic studies (Schroeder et al, 2005;IglesiasRodríguez et al, 2006). It is now conventionally recognized that E. huxleyi includes at least five morphologically discrete varieties or sub-species (Young et al, 2003).…”
mentioning
confidence: 88%
“…In the search for a genetic basis for this phenotypic variation, studies involving multiple E. huxleyi culture clones using molecular techniques such as RAPD and microsatellites have shown ample evidence of interclonal genotypic variation within the E. huxleyi morpho-species (Medlin et al, 1996, Iglesias-Rodriguez et al, 2006. One study has correlated phenotypic and genotypic variation, identifying a putative genetic marker for distinguishing E. huxleyi morphotypes (Schroeder et al, 2005). Pseudo-cryptic species have been documented in several coccolithophore taxa, with molecular data supporting earlier morphological and geological evidence (Sáez et al, 2003), but for E. huxleyi the question of whether different phenotypes or genotypes represent reproductively isolated species or interbreeding populations within a species complex remains to be resolved.…”
Section: The Origin Of Strain-specific Responsesmentioning
confidence: 99%